Experimental Study on Streptococcus agalactiae Genotype and Erythromycin Resistance in Neonatal Sepsis - Shen, Lijuan; Huang, Manqian; Xie, Nanli (Cellular and Molecular Biology, 2022)
This study aimed to evaluate Streptococcus agalactiae genotype and erythromycin resistance in neonatal sepsis. After obtaining the mothers’ informed consent, trained nurses sampled 430 neonatal specimens of sepsis from the ear canal, oral cavity and umbilical cord immediately after childbirth and implemented a cross-sectional study. By Gram staining, morphology, hemolysis mode, catalase and CAMP tests, the isolate was identified as S. agalactiae. All 455 isolates were tested for antimicrobial susceptibility by the disc diffusion method. Multilocus sequence typing was used to serotype S. agalactiae involving sequencing of 7 housekeeping genes. The erythromycin resistance genes-erm (B), erm (A) and mef (A) were detected by PCR. Results showed that there were 286 cases (66.51%) of neonates delivered naturally, and 144 cases (33.49%) of neonates delivered by cesarean section. A total of 455 strains were tested, including 253 strains (55.60%) of Gram-positive bacteria with 100 strains (21.98%) of S. agalactiae and 52 strains (11.43%) of Staphylococcus epidermidis, 178 strains (39.12%) of Gram-negative bacteria with 45 strains of Klebsiella pneumoniae (9.89%), 36 strains of Escherichia coli (7.91%), 36 strains of Pseudomonas aeruginosa (7.91%), and 323 strains of Citrobacter freundii (7.03%). S. agalactiae had the highest resistance of 87 (87.00%) to erythromycin, followed by resistance to azithromycin 83 (83.00%) and clindamycin 78 (78.00%). In children with neonatal sepsis, S. agalactiae serotypes were mainly Ia, Ib, and III, accounting for 29.00%, 35.00%, and 19.00% respectively. The main genotypes were ST651, ST103 and ST176, which account for 19.00%, 17.00% and 15.00% respectively. The ST19 type 13.00%, ST27 type 8.00%, ST17 Type 11.00%, ST10 type 12.00%, ST485 type 5.00%. The ST103 and ST485 isolates were classified as serotype Ia, the ST10 and ST176 isolates were classified as serotype Ib, and ST17 and ST19 isolates were classified as serotype III. Among the strains of S. agalactiae, 40.23% (35/87) carry erm (A) gene, 35.63% (31/87) carry erm (B) gene, and 24.14% (21/87) carry mef (A) gene. erm (A) gene was the most common gene in ST19 strain (7/11, 63.64%), and erm (B) gene was the most common gene in ST176 and ST651 strains (6/12, 50.00%; 8/18, 44.44%), while mef (A) gene was the most common gene in ST17 strain (5/11, 45.45%). In general, S. agalactiae genotypes in neonatal sepsis were mainly ST651, ST103 and ST176, and the main serotypes are Ia, Ib, and III. There was good consistency between ST and serotype, and a significant difference was shown in erythromycin resistance and ST distribution, which highlights the value of new epidemiological trend detection by monitoring multiple characteristics and provides inspiration for the development of multivalent S. agalactiae vaccines.